ANALISIS FINANCIAL LEVERAGE, PROFITABILITAS DAN EARNING PER SHARE (EPS) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ambarsari, Novie Dian; Sidiq, Ahmad (JURNAL RISET MANAJEMEN & AKUNTANSI, 2013)
The purpose of this research to know âIs financial leverage, profitabilitas, earning per share affect toward corporate value of manufactory industry at Jakarta Stock Exchange parstially and simultaneously. This research use multiple regression analysis and to be examined hypothesis to partially and F simultaneously. It is total sample 43 corporate at Jakarta Stock Exchange period 2009-20011. The result management research that Financial leverage in fact toward corporate value, profitability and earning per share in fact do not affect toward corporate value Jakarta Stock Exchange. Financial leverage, profitabilitas and earning per share in affect simultaneously toward corporate value at Jakarta Stock Exchange.